INTRODUCTION TO RED GINGER PROCESSING AS A HEALTH DRINK FOR WOMEN WITH REPRODUCTIVE HEALTH DISORDERS IN PETERONGAN JOMBANG - Mudrikatin, Siti; Yastutik, Iryani Yuni; Setyowati, Risha (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
This community service program aimed to improve knowledge and practical skills among women regarding the processing of red ginger (Zingiber officinale var. rubrum) as a health beverage to support reproductive health and immune function. The activity was conducted in Jabon Village, Jombang Regency, involving 25 participants. The intervention consisted of health education, interactive discussion, and a hands-on demonstration session. Program evaluation was carried out using a pre-test and post-test questionnaire to assess participants’ knowledge. The results showed an increase in the mean knowledge score from 62.4 (pre-test) to 84.7 (post-test), indicating a significant improvement in participants’ understanding of the benefits and processing methods of red ginger. Participants were also able to independently demonstrate the preparation of red ginger beverages. In addition, the program enhanced participants’ awareness of the economic potential of herbal products as home-based business opportunities. In conclusion, the combination of education and practical demonstration is effective in improving community knowledge and skills. Further follow-up programs are recommended to ensure sustainability and long-term impact.